2007
DOI: 10.1530/eje-07-0136
|View full text |Cite
|
Sign up to set email alerts
|

Recent outcome of Graves’ disease patients with papillary thyroid cancer

Abstract: Objective: The objective was to evaluate the clinical behavior and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
4
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 15 publications
8
63
4
7
Order By: Relevance
“…These data support the hypothesis that immune responses may influence DTC progression (Gupta et al 2001, Yano et al 2007, Muzza et al 2010. In fact, pathologists have long recognized that some tumors are densely infiltrated by cells of both innate and adaptive arms of the immune system, thereby reflecting inflammatory conditions arising in non-neoplastic tissues.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…These data support the hypothesis that immune responses may influence DTC progression (Gupta et al 2001, Yano et al 2007, Muzza et al 2010. In fact, pathologists have long recognized that some tumors are densely infiltrated by cells of both innate and adaptive arms of the immune system, thereby reflecting inflammatory conditions arising in non-neoplastic tissues.…”
Section: Introductionsupporting
confidence: 77%
“…Immune responses against differentiated thyroid carcinomas (DTCs) have long been demonstrated (Matsubayashi et al 1995, Modi et al 2003 and associations between inflammatory microenvironment and DTCs repeatedly reported (Yano et al 2007, Muzza et al 2010, evidenced by a mixture of lymphocytes and macrophages frequently found within and inside or surrounding primary thyroid tumors (Modi et al 2003, French et al 2010. These data support the hypothesis that immune responses may influence DTC progression (Gupta et al 2001, Yano et al 2007, Muzza et al 2010.…”
Section: Introductionmentioning
confidence: 56%
“…The outcome may suggest that small carcinomas in Graves' patients have the same prognosis as larger carcinomas in euthyroid patients. Yano et al compared the features of 154 cases of papillary thyroid cancers diagnosed in patients with Graves' disease to a euthyroid group with thyroid cancer [ 46 ] and did not fi nd signifi cant diff erences in multifocality, lymph node metastases, or distant metastases between the Graves' disease and the euthyroid group. Edmonds et al, in their study with 502 patients with thyroid cancer, reported similar mortality rates when comparing patients with Graves' disease and with multinodular goiter to that of euthyroid patients matched for age [ 45 ] .…”
Section: Aggressivenessmentioning
confidence: 99%
“…Although not all studies are in agreement, a meta-analysis of ten studies showed a 2.77-fold increased incidence of thyroid cancer in patients with antibody evidence of Hashimoto's thyroiditis, compared with control populations (Singh et al 1999). Similar to the controversy in Hashimoto's thyroiditis, there is an ongoing debate about the association between Graves' disease and thyroid cancer incidence, and aggressiveness (Filetti et al 1988, Hales et al 1992, Pellegriti et al 1998, Yano et al 2007. Because Hashimoto's is often associated with progression to hypothyroidism and thus elevated serum TSH concentration and because TSH receptor stimulation is crucial to the pathogenesis of Graves' disease, it is possible that humoral thyroid autoimmunity is linked to thyroid cancer through the TSH receptor.…”
Section: Autoimmune Thyroid Disease and Thyroid Cancermentioning
confidence: 99%